2021
DOI: 10.1242/jcs.258332
|View full text |Cite
|
Sign up to set email alerts
|

DNA binding alters ARv7 dimer interactions

Abstract: Androgen receptor (AR) splice variants are described as one of the potential drivers of lethal castration-resistant prostate cancer. Androgen receptor splice variant 7 (ARv7) is the most commonly observed isoform and strongly correlates with resistance to second-generation antiandrogens. Despite this clinical evidence, the interplay between ARv7 and the highly expressed full-length AR (ARfl) remains unclear. In this work we show that ARfl/ARv7 heterodimers readily form in the nucleus via an intermolecular N/C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
(99 reference statements)
0
6
0
Order By: Relevance
“…While these data indicate that ARv7 does not act predominantly as a heterodimer with ARfl in VCaP16 cells, studies with ectopically expressed ARv7 clearly show it can act both as a homodimer and heterodimerize with ARfl (Kim et al, 2022;Ozgun et al, 2021;Roggero et al, 2021;Xu et al, 2015). A previous study in LNCaP95 cells (LNCaP cells adapted to androgen depleted medium) also found that DHT stimulation increased ARv7 chromatin binding, suggesting ARv7 heterodimerization with ARfl (Cato et al, 2019).…”
Section: Arv7 Binds Chromatin Independently Of Arflmentioning
confidence: 96%
“…While these data indicate that ARv7 does not act predominantly as a heterodimer with ARfl in VCaP16 cells, studies with ectopically expressed ARv7 clearly show it can act both as a homodimer and heterodimerize with ARfl (Kim et al, 2022;Ozgun et al, 2021;Roggero et al, 2021;Xu et al, 2015). A previous study in LNCaP95 cells (LNCaP cells adapted to androgen depleted medium) also found that DHT stimulation increased ARv7 chromatin binding, suggesting ARv7 heterodimerization with ARfl (Cato et al, 2019).…”
Section: Arv7 Binds Chromatin Independently Of Arflmentioning
confidence: 96%
“…20 different known AR-Vs which are truncated forms of the full-length AR (AR-FL) (Figure 2) (13, 16). Clinically relevant AR-Vs are almost always expressed with AR-FL and may coordinate gene expression via heterodimerisation (17,18). In the context of AR-FL, the LBD represses the AF1 function residing within the NTD when androgens are not bound to the LBD restricting its activation when the androgen trigger is absent (19).…”
Section: Ar Variantsmentioning
confidence: 99%
“…In most cases, AR-FL will homodimerise upon ligand activation and bind to DNA. Whilst it is widely agreed that AR-V7 will primarily heterodimerise with AR-FL, the protein can also homodimerise and have more transient DNA interactions (17,(37)(38)(39) (Figure 3). Özgün et al discovered that the genomic locations of heterodimers and AR-FL homodimers did not change but their chromatin binding dynamics were independent of each other (17), while AR-V7 homodimer DNAbinding locations have not been fully explored, although it has been determined that AR-Vs bind to constitutively open chromatin sites that are known to overlap AR-FL binding sites (40).…”
Section: Ar-v7mentioning
confidence: 99%
See 1 more Smart Citation
“…AR-FL/AR-V7 heterodimers readily form in the nucleus via intermolecular N/C (NTD-LBD) interactions. However, DNA binding occupancy is determined by protein monomers, not homodimer or heterodimer complexes [20].…”
Section: Introductionmentioning
confidence: 99%